Microalloyed preparation of pre-quenched core of fepcb nanocrystalline alloy and its application in iron core

CN117778892BActive Publication Date: 2026-10-16CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311845540.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-16
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

但是该合金对制备过程质量的控制精度提出了更高的要求

Benefits of technology

[0020] ①Fe in this invention 86-x P 11 C2B1Cux The preparation method of nanocrystalline alloy utilizes microalloying techniques, adding Cu element at an atomic concentration of 0.2-1.0%. By fully leveraging the nucleation effect of heterogeneous elements and the inhibitory effect of in-situ precipitated P clusters on grain coarsening, a nanocrystalline alloy with pre-existing quenched nuclei was prepared, successfully obtaining a nanocrystalline alloy with α-Fe grains exhibiting excellent soft magnetic properties and extremely high heat treatment stability. Further reducing the coercivity Hc and widening the heat treatment window, the heating time during annealing heat treatment can be extended to 240 min. Using the nanocrystalline alloy strips of this invention to fabricate iron cores, and subsequently applying them to various transformers, can reduce iron losses and improve energy utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117778892B_ABST
    Figure CN117778892B_ABST
Patent Text Reader

Abstract

The application discloses a microalloyed preparation pre-existing quenched nucleus FePCB nanocrystalline alloy and application thereof in an iron core, Fe 86‑x P 11 C2B1Cu x , x = 0.2-1.0, by means of microalloying and heat treatment, the mixing enthalpy of Cu and P is negative in the melt spin process, the mixing enthalpy of P and Fe is also negative, the Cu-P cluster is decomposed in isothermal annealing, partial Cu is precipitated and leaves partial enriched P cluster, partial in-situ precipitated nanometer Cu phase and the nanometer Fe a P b C c B d Cu e phase in the amorphous Fe matrix compete for nucleation activation, and the significant increase of nucleation sites inhibits the excessive growth of single alpha-Fe grain. The pre-existing quenched nucleus Fe 86‑ x P 11 C2B1Cu x nanocrystalline alloy prepared by the method has the application to the transformer iron core, has lower coercive force while keeping high saturation magnetization, and reduces the transformer no-load loss by 75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to materials used as transformer cores, and more particularly to a core of a FePCB nanocrystalline alloy with a pre-stored quenched core, and a method for preparing the FePCB nanocrystalline alloy with a pre-stored quenched core using microalloying. Background Technology

[0002] A transformer is an electrical appliance that uses the principle of electromagnetic induction to transform high voltage into low voltage or vice versa. Compared to traditional silicon steel core transformers, new energy-saving amorphous alloy core transformers have lower no-load losses and are widely recognized for their energy efficiency. The magnetic conductors of the core form the transformer's magnetic circuit, converting electrical energy in the primary circuit into magnetic energy, and vice versa; therefore, it is the medium for energy conversion. Furthermore, the core is surrounded by windings that support the leads, and almost all internal components of the transformer are housed on the core.

[0003] Amorphous alloys exhibit short-range order and long-range disorder in their atomic structure, and due to the absence of defects such as grain boundaries, phase boundaries, and dislocations, they display isotropic physical and chemical properties. These characteristics endow amorphous alloys with many excellent properties, such as mechanical properties, corrosion resistance, and magnetic properties, specifically low coercivity, high saturation magnetic induction, high permeability, and low ferromagnetic loss. Therefore, amorphous alloys can be applied in power distribution transformers, photovoltaic inverters, wind power converters, and on-board chargers, and have a broad application market and promising development prospects.

[0004] Fe-based amorphous alloys and Fe-based nanocrystalline alloys possess high permeability (Bs) and low coercivity (Hc), and their production cost is relatively low, making them "dual-green" materials in both production and application. Further promoting their application aligns with the current requirements for developing a green economy and improving energy efficiency. Researchers typically obtain quenched nanocrystalline Fe-based nanocrystalline alloys through compositional control or process design. Based on this strategy, researchers have designed nanocrystalline alloys with pre-existing quenched nuclei, exhibiting good ductility and magnetism. However, this alloy requires higher precision in controlling the quality of the preparation process.

[0005] Microalloying technology is a new metallurgical discipline that emerged in the international metallurgical community in the 1970s. Traditional microalloying technology is mainly used to process microalloyed steel. Microalloying refers to the low content of these elements in steel, typically below 0.1% (mass fraction). Elements commonly referred to as microalloying elements mostly include niobium (Nb), vanadium (V), titanium (Ti), boron (B), aluminum (Al), and rare earth elements (RE). Unlike unwanted residual elements in steel, microalloying elements are intentionally added to improve the properties of the steel. Alloying elements and microalloying elements differ not only in content but also in their metallurgical effects: alloying elements primarily affect the steel matrix, while microalloying elements, besides the dragging effect of solute atoms, almost always affect the microstructure of the steel through the precipitation of a second phase. Summary of the Invention

[0006] To reduce the iron loss of current silicon steel sheet transformer cores, this invention proposes a FePCB nanocrystalline alloy material with a pre-stored quenched core for use in transformer cores. 86-x P 11 C2B1Cu x With x = 0.2-1.0, using microalloying and heat treatment, the nucleation effect of heterogeneous elements and the inhibitory effect of in-situ precipitated P clusters on grain coarsening were utilized. Microalloying of Cu in a high-Fe, P-rich alloy system yielded a nanocrystalline alloy with pre-existing quenched nuclei possessing excellent comprehensive soft magnetic properties and superior heat treatment stability. A Cu-P cluster synergistic mechanism was also proposed. During melt spin quenching, the mixing enthalpy of Cu and P is negative, as is the mixing enthalpy of P and Fe. During isothermal annealing, Cu-P clusters decompose, with some Cu precipitating and leaving locally enriched P clusters. Some in-situ precipitated nano-Cu phases merge with amorphous Fe... a P b C c B d Cu e The nucleation activation competition between the precipitated and enriched Cu phases in the matrix, and the significant increase in nucleation sites, inhibited the excessive growth of individual α-Fe grains.

[0007] During annealing, phosphorus (P) can disperse immiscible elements, meaning that the decomposition of Cu-P clusters precipitates the nano-fcc-Cu phase. This, in turn, promotes heterogeneous nucleation of α-Fe and further improves the uniformity of α-Fe grains. Furthermore, the residual phosphorus-rich clusters significantly hinder the coarsening of α-Fe grains, resulting in a stable, uniform, and fine crystal morphology. Therefore, the formation and in-situ decomposition mechanism of Cu-P clusters is of significant value in guiding the compositional design of iron-based nanocrystalline alloys with wide annealing temperature windows and ultra-high thermal stability.

[0008] In this invention, the chemical formula of the FePCBCu nanocrystalline alloy is Fea P b C c B d Cu e The Fe is α-Fe, where a, b, c, d, and e represent the percentage content of different atoms in the alloy, and a+b+c+d+e=100, where a is 85-85.8, b is 11, c is 2, d is 1, and e is 0.2-1.0.

[0009] Furthermore, the Fe a P b C c B d Cu e The coercivity Hc of the nanocrystalline alloy is 1.2 A / m to 9.0 A / m, and the saturation magnetization Bs is 1.50 T to 1.90 T.

[0010] The second objective of this invention is to propose a method for preparing FePCB nanocrystalline alloys with pre-existing quenched cores using microalloying. The preparation steps include: S1 master alloy melting; S2 strip preparation; S3 strip encapsulation; and S4 strip heat treatment.

[0011] Under the microalloying technology, immiscible Cu is introduced into Fe-P nanocrystalline alloy. By utilizing the carrier effect of P on Cu, i.e. through the decomposition of Cu-P clusters, a large number of heterogeneous nucleation sites are generated, forming a residual P-rich phase that inhibits Fe coarsening. This achieves homogenization and refinement of α-Fe grains, greatly improving thermal stability and soft magnetic properties.

[0012] Furthermore, the master alloy smelting in step S1 is carried out according to Fe a P b C c B d Cu e The ingredients are labeled, where a, b, c, d, and e represent the atomic percentage (molar ratio) of each corresponding component, and a + b + c + d + e = 100, where a is 85-85.8%, b is 11%, c is 2%, d is 1%, and e is 0.2-1.0%. The raw materials are melted repeatedly in a high-vacuum electric arc melting furnace under an inert argon atmosphere to obtain a homogeneous alloy ingot.

[0013] Furthermore, the preparation of the strip in step S2 includes the following steps: the master alloy obtained from melting in step S1 is broken into small pieces, 4-5g of alloy ingot is placed in a quartz tube with a nozzle at the bottom opening, and the quartz tube is suspended and fixed in an induction coil. The distance between the nozzle and the copper wheel is adjusted, the power is turned on, and a suitable induced current is selected to heat the master alloy. Through the observation window, it is observed that the oxide scale on the surface of the melt is completely broken. Argon gas is introduced from the top of the quartz tube, and under a certain injection pressure, the alloy melt is sprayed onto a high-speed rotating copper wheel to prepare a continuous amorphous alloy thin strip with a thickness of about 20μm and a width of about 1mm, maintaining good mechanical properties. The coercivity of the strip obtained in step S2 is 10A / m to 25A / m, and the saturation magnetic intensity is 1.53T to 1.59T.

[0014] Furthermore, step S3, the tape encapsulation, specifically includes the following steps: cutting a certain length of the tape obtained in step S2, confirming that the cut portion of the tape has good surface quality, is collimated and bright, and placing it into a quartz tube; then installing the quartz tube on a sealing machine, drawing a vacuum, and finally obtaining a quartz tube sealed at both ends, with an internal vacuum and sealed containing the tape.

[0015] Furthermore, the heat treatment step S4 specifically includes the following steps: according to the target heat treatment temperature and time, set the temperature control program of the tube furnace, turn on the heating switch, and after the internal temperature of the tube furnace reaches the target temperature and is kept at that temperature for a period of time, send the quartz tube packaged in step three into the tube furnace. After heat treatment for a period of time, take out the packaged quartz tube and cool it in the air. Repeat the above process until all samples have completed heat treatment.

[0016] Furthermore, the temperature control program for the tubular furnace in step S4 is specifically as follows: the heating rate is 10K / min to 15K / min, and the heat treatment temperature is 300℃ to 500℃.

[0017] Furthermore, the heat treatment time in step S4 is 10-240 min.

[0018] A third objective of this invention is the application of FePCB nanocrystalline alloys with pre-stored quenched cores exhibiting low coercivity in transformer cores. The FePCB nanocrystalline alloys with pre-stored quenched cores prepared by the method of this invention... 86-x P 11 C2B1Cu x When nanocrystalline alloys are applied to transformer cores, they maintain high saturation magnetization while exhibiting low coercivity, thus reducing transformer no-load losses by 50% to 75%.

[0019] Technical effects of the present invention:

[0020] ①Fe in this invention 86-x P 11 C2B1Cux The preparation method of nanocrystalline alloy utilizes microalloying techniques, adding Cu element at an atomic concentration of 0.2-1.0%. By fully leveraging the nucleation effect of heterogeneous elements and the inhibitory effect of in-situ precipitated P clusters on grain coarsening, a nanocrystalline alloy with pre-existing quenched nuclei was prepared, successfully obtaining a nanocrystalline alloy with α-Fe grains exhibiting excellent soft magnetic properties and extremely high heat treatment stability. Further reducing the coercivity Hc and widening the heat treatment window, the heating time during annealing heat treatment can be extended to 240 min. Using the nanocrystalline alloy strips of this invention to fabricate iron cores, and subsequently applying them to various transformers, can reduce iron losses and improve energy utilization efficiency.

[0021] ② The microalloying method in the heat treatment process provided by this invention can rapidly and mass-produce nanocrystalline alloys with excellent comprehensive soft magnetic properties. It has low preparation cost and significantly improved performance, which can meet the demand for nanocrystalline alloy materials in the energy, power and electronics fields.

[0022] ③Fe in this invention 86-x P 11 C2B1Cu x Nanocrystalline alloys possess extremely high thermal stability and low coercivity. Attached Figure Description

[0023] Figure 1 This is a flowchart illustrating the synergistic mechanism of Cu-P on α-Fe grain homogenization during annealing.

[0024] Figure 2 quenched Fe 86-x P 11 C2B1Cu x XRD pattern of nanocrystalline alloy.

[0025] Figure 3 quenched Fe 86-x P 11 C2B1Cu x DSC curves of nanocrystalline alloys.

[0026] Figure 4 quenched Fe 86-x P 11 C2B1Cu x The coercivity H of nanocrystalline alloys after heat treatment at 300℃-500℃ for 10 min c and saturation magnetization B s .

[0027] Figure 5 For Fe 85.4 P 11 C2B1Cu 0.6 Heat treatment time and H of nanocrystalline alloys cand B s A schematic diagram.

[0028] Figure 6 For Fe 85.4 P 11 C2B1Cu 0.6 TEM bright-field image of nanocrystalline alloy.

[0029] Figure 7 For annealing Fe 85.4 P 11 C2B1Cu 0.6 The relationship between magnetization and iron loss in nanocrystalline alloys.

[0030] Figure 8 For Fe 85.4 P 11 C2B1Cu 0.6 A physical image of a nanocrystalline alloy iron core.

[0031] Figure 9 For Fe 85.4 P 11 C2B1Cu 0.6 SAED image of nanocrystalline alloy.

[0032] Figure 10 For Fe 85 P 11 TEM bright-field image of C2B1Cu1 nanocrystalline alloy.

[0033] Figure 11 Cu in quenched state 1.0 High-resolution images and SAED diagrams of the alloy.

[0034] Figure 12 For Fe 85 P 11 Heat treatment time and H of C2B1Cu1 nanocrystalline alloy c and B s A schematic diagram. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only a part of the present invention and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0036] The FePCBCu nanocrystalline alloy used as the transformer core in this invention has the chemical formula Fe. a P b C c B d Cu eThe Fe is α-Fe, where a, b, c, d, and e represent the percentage content of different atoms in the alloy, and a+b+c+d+e=100, where a is 85-85.8, b is 11, c is 2, d is 1, and e is 0.2-1.0.

[0037] Fe in this invention a P b C c B d Cu e Nanocrystalline alloys, with adjusted composition and dosage. After preheating a tube furnace, a heating rate (10 K / min to 15 K / min) and a heating temperature (300°C to 500°C) are set, and the alloy is held at these intervals (300°C to 500°C) for 5 to 15 minutes. The interval heating temperature is 10°C to 30°C. Fe obtained through the microalloying and heat treatment methods of this invention... a P b C c B d Cu e On the one hand, the enthalpy of mixing of Cu and P is negative during melt spin quenching, and they tend to spontaneously combine to form Cu-P clusters during melt quenching; the enthalpy of mixing of P and Fe is also negative, and P can be uniformly distributed in Fe. a P b C c B d Cu e In Fe, Cu can be uniformly distributed by forming Cu-P clusters through mechanical mixing of the melt. a P b C c B d Cu e In the middle. On the other hand, during isothermal annealing, Cu-P clusters decompose, some Cu precipitates and leaves locally enriched P clusters, and some in-situ precipitated nano-Cu phases and amorphous Fe a P b C c B d Cu e The nucleation activation competition between the precipitated and enriched Cu phases in the middle stage, and the significant increase in nucleation sites, inhibited the formation of individual α-Fe grains. Figure 5 , Figure 6 Excessive growth of α-Fe grains is hindered. The localized P-rich clusters left by Cu precipitation severely impede Fe diffusion during annealing, suppressing the coarsening of α-Fe grains. During isothermal annealing, P acts as a crucial "binder" and "dispersant" for heterogeneous elements, fundamentally improving the growth of Fe. a P b C c B d Cue The thermal stability of nanocrystalline alloys enhances Fe a P b C c B d Cu e Robustness in the production of transformer core materials.

[0038] This invention pre-stores Fe in quenched state nuclei a P b C c B d Cu e The permeability, coercivity, and hysteresis loss of nanocrystalline alloys depend on the alloy's composition design, processing method, and heat treatment regime. These will be described in detail below through examples.

[0039] Example 1

[0040] Microalloying to prepare Fe with pre-stored quenched core 85.4 P 11 C2B1Cu 0.6 Nanocrystalline alloys

[0041] S1, master alloy smelting;

[0042] Fe is prepared according to atomic percentage content. 85.4 P 11 C2B1Cu 0.6 Element.

[0043] Microalloying is carried out in an inert protective gas (Ar) atmosphere by heating in an argon atmosphere in a high vacuum induction melting furnace to ensure that the alloy is fully and uniformly melted. After repeated melting, the alloy ingot is cooled to room temperature and taken out.

[0044] Melting parameters: The protective atmosphere for melting is argon gas with a mass percentage of 99.999%;

[0045] Vacuum degree is 8×10 -3 Pa;

[0046] The melting current is 200A;

[0047] Melting time: 5 minutes per melting cycle, 5 melting cycles;

[0048] S2, strip preparation;

[0049] Strip material is prepared using a single-roller spinning and quenching machine. The master alloy obtained from melting in step S1 is broken into small pieces and placed in a quartz tube. Eddy currents are generated by an induction coil to melt the alloy blocks. After the alloy is completely melted, the injection key is pressed. Under the action of the pressure difference between the upper and lower parts of the nozzle, the alloy melt is sprayed from the nozzle into a rapidly rotating copper roller directly below in an argon atmosphere. The melt is rapidly cooled on the surface of the copper roller to obtain a continuous quenched strip.

[0050] Parameter settings: The protective atmosphere for melting is argon gas with a mass percentage of 99.0%;

[0051] Vacuum degree: 5×10 -3 Pa;

[0052] The coil induced current is 8A;

[0053] Melting time: 20s;

[0054] Copper wheel rotation speed: 2600m / s;

[0055] The JEM-2100F transmission electron microscope was used for inspection, such as... Figure 6 The image shown is a TEM image of the tape obtained in step S2, illustrating the presence of pre-existing α-Fe nanocrystals in the tape.

[0056] like Figure 9 The quenched Cu shown 0.6 SAED pattern of the alloy. The image shows diffraction rings of α-Fe grains, with the inner ring representing the Cu3P phase. The results indicate that Cu... 0.6 The Cu in the alloy exists in the form of amorphous Cu-P phase.

[0057] The coercivity of the strip obtained in step S2 is 10 A / m, and the saturation magnetic intensity is 1.59 T.

[0058] S3, strip packaging;

[0059] Cut a 7cm strip from the material obtained in step S2, confirm that the cut strip has good surface quality, is straight and bright, and has no stress-induced bending, and place it into a quartz tube; then install the quartz tube on a sealing machine, evacuate it, use a flame to aim at the quartz tube wall, slowly rotate the quartz tube to heat it evenly, the heated part softens and shrinks when heated, and finally obtain a quartz tube that is sealed at both ends, with an internal vacuum and the strip is sealed.

[0060] Vacuum level of quartz tube: 3×10 -1 Pa;

[0061] S4, heat treatment;

[0062] A TSK 1400 tubular heat treatment furnace was selected for processing. Figure 1 The process shown involves heat treatment. First, the tube furnace is preheated and heated to 360°C at a heating rate of 10 K / min. Then, the quartz tube with sealed strips obtained in step S3 is placed into the tube furnace and held at 360°C for 10 min. After that, it is removed and cooled in air to obtain Fe. 85.4 P 11 C2B1Cu 0.6 Nanocrystalline alloy.

[0063] exist Figure 1 In the annealing process, Cu-P clusters play a crucial role in improving the thermal stability and optimizing the soft magnetic properties of Fe-based nanocrystalline alloys with α-Fe nanocrystals. The enthalpy of mixture of Cu and P is negative, therefore they tend to spontaneously combine to form Cu-P clusters during melt quenching. Simultaneously, the enthalpy of mixture of P and Fe is also negative, allowing P to be uniformly distributed in the alloy without severe segregation. Cu can be uniformly distributed in the alloy by forming Cu-P clusters through the mixing of the melt. Due to the low solid solubility of Cu in Fe, Cu-P clusters decompose, some Cu precipitates, leaving locally enriched P clusters. These locally enriched phosphorus clusters left by Cu precipitation severely hinder the element diffusion process and suppress the coarsening of α-Fe grains, which is also a key factor in maintaining the alloy's extremely high thermal stability.

[0064] Performance testing and results

[0065] XRD patterns: Detected using a D / MAX-2500PC device. Figure 2 Explanation of Fe 85.4 P 11 C2B1Cu 0.6 It is an amorphous nanocrystalline alloy.

[0066] DSC curve: Detected using a NETZSCH DSC 404C device, from... Figure 3 Determining Fe 85.4 P 11 C2B1Cu 0.6 The heat treatment temperature, and two peaks (first crystallization temperature T). X1 Second crystallization temperature T X2 The greater distance between them indicates a wider range of annealing temperatures, which is beneficial for optimizing magnetic properties.

[0067] Magnetic properties: Coercivity H was tested using a soft magnetic DC hysteresis loop apparatus (DC-BH). c B was tested using a vibrating sample magnetometer (VSM). s Magnetic properties were tested using a Lake Shore 7407 vibrating sample magnetometer and a MATS-2010SA (Hunan Lianzhong) DC-BH hysteresis loop analyzer. The test results of Example 1 show that the addition of 0.6% Cu can significantly reduce H... c (minimum H) c Only 1.2 A / m (Ta = 360℃), increasing the saturation magnetization B s It is 1.66T, see Figure 4 , Figure 5As shown, through isothermal heat treatment, α-Fe grains gradually grow, the grain size gradually becomes smaller and more uniform, and the crystallization volume fraction increases, thus Hc decreases and Bs increases.

[0068] Figure 7 The graph shows the relationship between magnetization and iron loss in annealed samples. As the saturation magnetization increases, the iron loss gradually increases, and the Fe... 85.4 P 11 C2B1Cu 0.6 The Bs of amorphous nanocrystals after treatment at 633K for 10 min is 1.66T, indicating low iron loss.

[0069] A core with an inner diameter of 20mm, an outer diameter of 30mm, a height of 10mm, and a weight of 20±0.5g was prepared using a HY-PMHJ type core winding machine. Figure 8 As shown.

[0070] Will Figure 8 The iron core shown is used in a transformer (Transformer A). Compared to a transformer with a silicon steel core (Transformer B), Transformer A's no-load loss is reduced by 75%, equivalent to 20-25% of Transformer B's. No-load loss refers to the active power consumed when the secondary winding of a transformer is open-circuited and the primary winding is subjected to a rated voltage of a sinusoidal waveform at the rated frequency. No-load loss is a constant loss. It is independent of the current passing through it but related to the voltage across the component. Many factors affect the no-load performance of a transformer, such as the material properties of the silicon steel sheets, the processing technology and equipment, and the structural form of the iron core.

[0071] Example 2

[0072] The difference between Example 2 and Example 1 is that the heating temperature set in the S4 heat treatment is different, but the holding time is the same (10 min).

[0073] S4, heat treatment;

[0074] See Figure 1 As shown, heat treatments were performed at heating temperatures of 300℃, 320℃, 340℃, 380℃, 400℃, 420℃, 440℃, 460℃, 480℃, and 500℃. Fe 85.4 P 11 C2B1Cu 0.6 The coercivity H of nanocrystalline alloys c and saturation magnetization B s like Figure 4 As shown, the optimal coercivity Hc is 1.2 A / m, and the optimal saturation magnetization Bs is 1.87 T.

[0075] A core with an inner diameter of 20 mm, an outer diameter of 30 mm, a height of 10 mm, and a weight of 20 ± 0.5 g was prepared using a HY-PMHJ type core winding machine.

[0076] Fe 85.4 P 11 C2B1Cu 0.6 The use of iron cores in transformers reduces the no-load loss of transformers by 50% compared to silicon steel sheet transformers.

[0077] Example 3

[0078] The difference between Example 3 and Example 1 is that the heating temperature set in the S4 heat treatment is the same, but the holding time is different.

[0079] S4, heat treatment;

[0080] See Figure 1 As shown, the holding times were 50 min, 100 min, 150 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min, and 500 min, respectively. Fe 85.4 P 11 C2B1Cu 0.6 The coercivity H of nanocrystalline alloys c and saturation magnetization B s like Figure 5 As shown, the optimal coercivity Hc is 1.2 A / m, and the optimal saturation magnetization Bs is 1.72 T.

[0081] The strips obtained after heat treatment in step S4 above were then measured, and their magnetic properties were measured after heat treatment at different times and temperatures. The coercivity H was tested using a soft magnetic DC hysteresis loop analyzer (DC-BH). c B was tested using a vibrating sample magnetometer (VSM). s The measurement result is the average of multiple measurements. The test results of Example 3 show that B... s Overall, it shows a fluctuating upward trend, H c First lower, t a = Reaches its lowest value of 1.2 A / m at 10 min, t a The temperature rises slowly and then tends to stabilize after 60 minutes. 0.6 The alloy also exhibited good overall soft magnetic properties and excellent thermal stability after annealing at 633K for 480 min, and its H c and B s The values ​​are 11.9 A / m and 1.72 T, respectively. See Figure 5 .

[0082] A core with an inner diameter of 20 mm, an outer diameter of 30 mm, a height of 10 mm, and a weight of 20 ± 0.5 g was prepared using a HY-PMHJ type core winding machine.

[0083] Fe 85.4 P 11 C2B1Cu 0.6 The use of iron cores in transformers reduces the no-load loss of transformers by 60% compared to silicon steel sheet transformers.

[0084] Example 4

[0085] Microalloying to prepare Fe with pre-stored quenched core 85 P 11 C2B1Cu1 nanocrystalline alloy

[0086] S1, master alloy smelting;

[0087] Fe is prepared according to atomic percentage (molar ratio) content. 85 P 11 C2B1Cu1 composition.

[0088] Microalloying is carried out in an inert protective gas (Ar) atmosphere by heating in an argon atmosphere in a high vacuum induction melting furnace to ensure that the alloy is fully and uniformly melted. After repeated melting, the alloy ingot is cooled to room temperature and taken out.

[0089] Melting parameters: The protective atmosphere for melting is argon gas with a mass percentage of 99.999%;

[0090] Vacuum degree is 8×10 -3 Pa;

[0091] The melting current is 150A;

[0092] Melting time: 5 minutes per melting cycle, 4 melting cycles;

[0093] S2, strip preparation;

[0094] Strip material is prepared using a single-roller spinning and quenching machine. The master alloy obtained from the melting in step S1 is broken into small pieces and placed in a quartz tube. Eddy currents are generated by an induction coil to melt the alloy blocks. After the alloy is completely melted, the injection key is pressed. Under the action of the pressure difference between the upper and lower parts of the nozzle, the alloy melt is sprayed from the nozzle into a rapidly rotating copper roller directly below in an argon atmosphere. The melt is rapidly cooled on the surface of the copper roller to obtain a continuous strip material.

[0095] Parameter settings: The protective atmosphere for melting is argon gas with a mass percentage of 99.0%;

[0096] Vacuum degree: 2×10 -2 Pa;

[0097] The coil induced current is 8A;

[0098] Melting time: 25s;

[0099] Copper wheel rotation speed: 2600m / s;

[0100] The JEM-2100F transmission electron microscope was used for inspection, such as... Figure 10 The image shown is a TEM image of the tape obtained in step S2. The image shows that there are a large number of fine α-Fe particles in the amorphous matrix of the tape, and the average size of the grains is 21.1 nm.

[0101] like Figure 11 The quenched Cu shown 1.0 SAED pattern of the alloy. The image shows clear diffraction spots of fcc-Cu, representing the Cu <0, -1, 1> plane. Diffraction rings of α-Fe grains are present, with the inner ring representing the Cu3P phase. The results indicate that Cu... 1.0 The existence of Cu in the alloy can be divided into three parts: the first part is Cu in the amorphous matrix, the second part is Cu in the amorphous Cu-P phase, and the third part is Cu clusters that are precipitated and enriched.

[0102] The coercivity of the strip obtained in step S2 is 24 A / m, and the saturation magnetic intensity is 1.58 T.

[0103] S3, strip packaging;

[0104] Cut the strip obtained in step S2 to a length of 8cm. Confirm that the surface quality of the cut strip is good, it is straight and bright, and there is no bending caused by stress. Place it into a quartz tube. Then install the quartz tube on a sealing machine, evacuate it, use a flame to aim at the wall of the quartz tube, slowly rotate the quartz tube to heat it evenly. The heated part softens and shrinks due to heat. Finally, a quartz tube with both ends closed and the inside vacuum sealed with the strip is obtained.

[0105] Vacuum level of quartz tube: 3×10- 1 Pa;

[0106] S4, heat treatment;

[0107] See Figure 1 As shown, the tube furnace is first preheated to 400°C at a heating rate of 12 K / min; then, the quartz tube with sealed strips obtained in step S3 is fed into the tube furnace and held at 400°C for 10 min, then removed and cooled in air to obtain Fe. 85 P 11 C2B1Cu1 nanocrystalline alloy.

[0108] exist Figure 1During the annealing process, due to the low solid solubility of Cu in Fe, Cu-P clusters decompose. Driven by thermally activated diffusion, some Cu precipitates, leaving behind locally enriched P clusters. The partially precipitated nano-Cu phase competes with the nucleation and activation of the Cu phase precipitated and enriched from the amorphous matrix, and the significant increase in nucleation sites inhibits the excessive growth of individual α-Fe grains. Simultaneously, the locally enriched phosphorus clusters left by Cu precipitation severely hinder the elemental diffusion process and suppress the coarsening of α-Fe grains, which is a key factor in maintaining the alloy's extremely high thermal stability.

[0109] Performance testing and results

[0110] XRD patterns: Detected using a D / MAX-2500PC device. Figure 2 Explanation of Fe 85 P 11 C2B1Cu1 is an amorphous nanocrystalline alloy.

[0111] DSC curve: Detected using a NETZSCH DSC 404C device, from... Figure 3 Determining Fe 85 P 11 The temperature of C2B1Cu1 heat treatment and the large distance between the two peaks indicate a wide range of annealing temperatures, which is beneficial for optimizing magnetic properties.

[0112] Magnetic properties: Coercivity H was tested using a soft magnetic DC hysteresis loop apparatus (DC-BH). c B was tested using a vibrating sample magnetometer (VSM). s The test results of Example 4 show that the addition of 1.0% Cu can significantly reduce H. c (minimum H) c Only 8.0 A / m (Ta = 400℃), improving B s And the saturation magnetization is 1.79T, see Figure 12 As shown.

[0113] A core with an inner diameter of 20 mm, an outer diameter of 30 mm, a height of 10 mm, and a weight of 20 ± 0.5 g was prepared using a HY-PMHJ type core winding machine.

[0114] Fe 85 P 11 The C2B1Cu1 core is used in transformers, which reduces the no-load loss of the transformer by 58% compared to silicon steel sheet transformers.

[0115] Example 5

[0116] The difference between Example 5 and Example 4 is that the heating temperature set in the S4 heat treatment is 380°C, and the holding time is different.

[0117] S4, heat treatment;

[0118] See Figure 1 As shown, the heat preservation times were 5 min, 10 min, 20 min, 30 min, 60 min, 120 min, 180 min, and 240 min, respectively. Fe 85 P 11 The coercivity H of C2B1Cu1 nanocrystalline alloy c and saturation magnetization B s like Figure 12 As shown, the optimal coercivity Hc is 8.2 A / m, and the optimal saturation magnetization Bs is 1.77 T.

[0119] A core with an inner diameter of 20 mm, an outer diameter of 30 mm, a height of 10 mm, and a weight of 20 ± 0.5 g was prepared using a HY-PMHJ type core winding machine.

[0120] Fe 85 P 11 The C2B1Cu1 core is used in transformers, which reduces the no-load loss of the transformer by 50% compared to silicon steel sheet transformers.

[0121] Example 6

[0122] The difference between Example 6 and Example 4 is that the heating temperature set in the S4 heat treatment is 440°C, and the holding time is different.

[0123] S4, heat treatment;

[0124] See Figure 1 As shown, the heat preservation times were 5 min, 10 min, 20 min, 30 min, 60 min, 120 min, 180 min, and 240 min, respectively. Fe 85 P 11 The coercivity H of C2B1Cu1 nanocrystalline alloy c and saturation magnetization B s like Figure 12 As shown, the optimal coercivity Hc is 5.5 A / m, and the optimal saturation magnetization Bs is 1.78 T.

[0125] A core with an inner diameter of 20 mm, an outer diameter of 30 mm, a height of 10 mm, and a weight of 20 ± 0.5 g was prepared using a HY-PMHJ type core winding machine.

[0126] Fe 85 P 11 The C2B1Cu1 core is used in transformers, which reduces the no-load loss of the transformer by 55% compared to silicon steel sheet transformers.

Claims

1. A FePCB nanocrystalline alloy with a pre-stored quenched core for use as a transformer core, characterized in that: Chemical formula is Where a, b, c, d, and e represent the molar percentage content of different atoms in the alloy, Where a is 85-85.8, b is 11, c is 2, d is 1, and e is 0.6-1.0; Nanocrystalline alloys contain in the quenched state Nanocrystals, and coercivity is saturation magnetic intensity is ; The microalloying method for the FePCB nanocrystalline alloy with pre-stored quenched cores includes: S1 master alloy smelting; Microalloying was performed in an inert protective gas atmosphere using a high-vacuum induction melting furnace under argon atmosphere, ensuring thorough and uniform alloy melting. After repeated melting processes, the alloy ingot was cooled to room temperature and removed. The melting vacuum degree was [value missing]. The smelting current is ; Preparation of S2 strip; Strip material was prepared using a single-roller spinning and quenching machine. The coil induced current was 8A, and the copper wheel rotation speed was [missing information]. ; S3 tape packaging; and S4 strip heat treatment; The heating rate of the tubular heat treatment furnace is The heat treatment temperature is The heat treatment time is ; prepared Nanocrystalline alloys contain in the quenched state Nanocrystals.